Fundraising Zakat Ditinjau Dari Filsafat Ekonomi Islam (Landasan Ontologi, Epistomologis, dan Aksiologis) Filsafat Ilmu - Ilham, Muhammad Satriana (CV Widina Media Utama, 2024)
The theories used by the author are theories about the scope of zakat, the scope around zakat fundraising and the theory of receiving zakat funds. The theory of zakat discusses the meaning of zakat, the legal basis of zakat, the history of zakat management in Indonesia. In the scope of zakat fundraising, it discusses the definition of fundraising strategy, the relationship between fundraising and marketing, methods, principles, elements, OPZ fundraising strategies, and OPZ fundraising goals. In the theory of receiving zakat funds, it discusses the factors that influence muzzaki in deciding to give zakat to LAZ. The method used in this article is the library research method. The library sources used are books and articles related to this article. The analysis used in this article is content analysis. First, identifying various related sources for the purpose of writing the article. Second, conducting content analysis techniques to find common threads from these various sources. Third, conclude or draw the final discussion of this research.ABSTRAKTeori yang digunakan oleh penulis adalah teori tentang ruang lingkup zakat, ruang lingkup seputar fundraising zakat dan teori penerimaan dana zakat. Dalam teori zakat membahas mengenai pengertian zakat, dasar hukum zakat, sejarah pengelolaan zakat di Indonesia. Dalam ruang lingkup fundraising zakat dibahas pengertian strategi fundraising, hubungan fundraising dengan marketing, metode, prinsip, unsur-unsur, strategi fundraising OPZ, dan tujuan fundraising OPZ. Dalam teori penerimaan dana zakat di bahas mengenai faktor-faktor yang memengaruhi muzzaki dalam memutuskan untuk berzakat ke LAZ. Metode yang digunakan dalam artikel ini adalah metode kajian Pustaka atau library research. Sumber pustaka yang digunakan berupa buku dan artikel yang berkaitan dengan artikel ini. Analisis yang digunakan di dalam artikel ini adalah analisis isi atau content anlysis. Pertama, mengidentifikasi berbagai sumber yang terkait untuk kepentingan penulisan artikel. Kedua, melakukan teknik analisis isi untuk menemukan benang merah dari berbagai sumber tersebut. Ketiga, melakukan kesimpulan atau penarikan akhir pembahasan dari penelitian ini.